Methods of Organizing the Movement of Cars and Pedestrians on the Territory of the Newly Built Microdistrict on the Basis of Modern Requirements - Utkirovna, Taniyeva Komila (Journal of Ethics and Diversity in International Communication, 2021)
In this article, we will have the opportunity to get acquainted in detail with the methods of organizing the movement of cars and pedestrians in the territory of the modern microdistrict under construction and the instructions for its organization.